An integrated microspectrometer for localised multiplexing measurements - Hu, Z.; Glidle, A.; Ironside, Charlie; Cooper, J.; Yin, H. (Royal Society of Chemistry, 2015)
We describe the development of an integrated lensed Arrayed Waveguide Grating (AWG) microspectrometer for localized multiplexing fluorescence measurements. The device, which has a footprint that is only 1 mm wide and 1 cm long, is capable of spectroscopic measurements on chip. Multiple fluorescence signals were measured simultaneously based upon simple intensity readouts from a CCD camera. We also demonstrate the integration of the AWG spectrometer with a microfluidic platform using a lensing function to confine the beam shape for focused illumination. This capability enhances signal collection, gives better spatial resolution, and provides a route for the analysis of small volume samples (e.g. cells) in flow. To show these capabilities we developed a novel "bead-AWG" platform with which we demonstrate localized multiplexed fluorescence detection either simultaneously or successively. Such an integrated system provides the basis for a portable system capable of optical detection of multi-wavelength fluorescence from a single defined location. This journal is